HUBUNGAN KUALITAS TIDUR DENGAN KECERDASAN EMOSIONAL SELAMA MASA PANDEMI COVID-19 PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Handro Steve Natanael, (2022)
Sleep quality may affect many important things in life. Medical students are one of the groups at risk of experiencing poor sleep quality, especially during the COVID-19 pandemic. Various stressors to medical students might cause poor sleep quality and affect emotional intelligence which is an important indicator of social functioning. The purpose of this study was to determine the relationship between sleep quality and emotional intelligence during the COVID-19 pandemic in medical students. This research is a cross-sectional study. Data collection was done by a simple random sampling technique with a total sample of 120 respondents. Data based on the characteristics of respondents, univariate analysis, and bivariate analysis using the Spearman correlation test. The instruments used are the Pittsburgh Sleep Quality Index and the Schutte Emotional Intelligence Scale. The results of the bivariate analysis showed a p-value of 0.000 < 0.05 (α) and a calculated r-value of 0.674. Therefore, it can be concluded that there is a strong relationship between sleep quality and emotional intelligence in medical students during the COVID-19 pandemic. Keywords: Sleep Quality, Emotional Intelligence, COVID-19 Pandemic, Medical Students